Hot injection assisted electronically modulated twin and grain boundary rich sub-2 nm pt3co alloy resistant to phosphate ion for PEMFCs - Singh, Mayank U.; Jadhav, Swapnil D.; Shivankar, Bhavana R.; Pandikassala, Ajmal; Kumar, Yogesh; Krishnamurty, Sailaja; Vinod, C. P.; Kurungot, Sreekumar (Small, 2025)
Modulation of the electronic d-band center, structural defects (line defects), and particle size of Pt3Co alloy electrocatalyst have huge significance in elevating its electrochemical oxygen reduction reaction activity. Deviating from traditional high-temperature strategies, the current work focuses on ripening these benefits by implying a simple economically viable hot-injection-assisted modified polyol process. A conclusive control over decrementing particle size starting from 2.7 to 1.3 nm, an increasing degree of strain (twin boundary), and shifting of the d-band center away from the Fermi level are obtained via varying the temperature to which the solution is injected. The catalyst prepared via the injection at 200 degrees C (Pt3Co(1.3 t,g-b)/fVC-200) has delivered an electrochemical surface area of 84 m(2) g(Pt)(-1) with the onset and half-wave potentials of 0.980 and 0.858 V, respectively, versus RHE and a limiting current of -6.0 mA cm(-2) with stability till 20k cycles. In the high-temperature proton exchange membrane fuel cell Pt3Co(1.3 t,g-b)/fVC-200-based cell has outperformed Pt/C rendering 600 mWcm(-2) under H-2-Air compared to 529 mWcm(-2) of Pt/C with 20% lower Pt loading and double the stability due to enhanced resistance toward phosphoric acid for accelerated voltage cycling. A similar enhancement is seen while employing the catalyst for low-temperature fuel cells.
Keywords: electrocatalyst; grain boundary; hot injection synthesis; modified polyol process; oxygen reduction reaction; proton exchange membrane fuel cell; Pt3Co alloy; twin boundary; valance band X-ray photoelectron spectroscopy

In situ engineered triple phase boundary enhancement in 3D structured carbon supported catalyst for high-temperature PEMFC - Pandikassala, Ajmal; Jadhav, Swapnil D.; Kurian, Maria; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
Enhancing platinum (Pt) utilization in polymer electrolyte membrane fuel cells (PEMFCs) requires optimizing the catalyst support microstructures to expand the triple-phase boundary (TPB). A promising method has been reported here which employs a three-dimensional (3D) catalyst support with an in situ-generated ionomer interface from preadmitted monomer molecules, potentially replacing the traditional Nafion ionomers. The small-sized monomers infiltrate the catalyst's pores, and UV curing polymerizes them into an extended interfacial network within the 3D carbon support. The single-cell analysis of the membrane electrode assemblies (MEAs) in high-temperature PEMFCs (HT-PEMFCs) using phosphoric acid-doped polybenzimidazole (PBI) membranes highlights the effectiveness of this approach. The strategy helps to achieve a current density of 1.06 A cm-2 and 0.49 A cm-2 at 0.60 V in H2-O2 and H2-air feed conditions, respectively. These values represent a significant improvement over the conventional Nafion ionomer-based MEAs, which exhibit current densities of 0.87 A cm-2 and 0.40 A cm-2 under H2-O2 and H2-air feeds, respectively, when utilizing a platinum-supported carbon (Pt/C) catalyst. When Pt nanoparticles are decorated on a high-surface-area, porous 3D interconnected carbon support synthesized via the carbonization of the polydopamine-coated melamine foam (Pt/3DPDC), the conventional Nafion ionomers tend to block the nanopores in the 3D carbon supports, leading to the underutilization of the Pt active sites. In contrast, the in situ ionomer approach enabled the system to deliver 0.93 A cm-2 at 0.60 V H2-O2 feed conditions, which is significantly higher than 0.38 A cm-2 obtained with the Nafion-based ionomers under similar conditions. This approach successfully makes use of the Pt active sites present in the nanopores and tackles the issues of mass transfer and reactant distribution, both of which are essential for expanding fuel cells from single cells to stacks. The exhibited method emphasizes how crucial it is to develop process-friendly electrocatalysts and complementary electrode manufacturing techniques in order to advance the PEMFC performance through a novel scientific path.

Pt-based 3D electrocatalyst with process-friendly features for PEMFCs possessing fast activation and improved mass-transfer properties - Pandikassala, Ajmal; Nadumattuvayil, Varsha; Singh, Mayank U.; Jadhav, Swapnil D.; Yoyakki, Athira; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Polymer-electrolyte-membrane fuel cells (PEMFCs) face the challenges like slow oxygen reduction reaction (ORR) kinetics and limited mass transport at high current densities, which affects their performance. The efficient water removal from the cathode is essential to improve oxygen diffusion. Addressing this, a catalyst is presented with platinum (Pt) nanoparticles distributed within a 3D carbon network (Pt/3DPDC) derived from the polydopamine-coated melamine foam. This unique architecture enhances Pt utilization and water management due to its high porosity and ample free spaces, providing a process-friendly feature for the electrode under PEMFC conditions. The pores and accessible texture of the 3D polydopamine derived carbon (3DPDC) framework facilitate ionomer uptake during the electrode fabrication, extending the active triple-phase boundary and improving the membrane electrode assembly (MEA) performance. The high porosity of Pt/3DPDC is mitigated by adding a small amount of commercial fuel cell catalayst (Pt/C), which maintains the effective catalyst number density per unit area by utilizing the excess porosity of the 3DPDC framework. This controlled interplay of the unique catalyst structure and spatially confined distribution of Pt/C within the Pt/3DPDC framework offers fast activation, reduced electrode flooding, and improved current densities across the operating potential window. This carefully engineered catalyst, designed through bottom-up strategies, is a promising electrocatalyst for practical PEMFC applications.
Keywords: Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable flexible zinc-air battery

A Pt-Based Carbon-Free Cathode with Embedded Oxygen Nanoreservoirs: A Promising Approach for Oxygen Buffering to Aid Oxygen Reduction Reactions of PEMFCs - Yoyakki, Athira; Kumar, Sachin; Pandikassala, Ajmal; Jadhav, Swapnil D.; Vinod, C. P.; Kurungot, Sreekumar (ACS Catalysis, 2025)
For practical applications of proton exchange membrane fuel cells (PEMFCs), the system needs to be operated by employing air in the cathode instead of pure oxygen (O2). This makes it necessary to develop innovative electrode engineering solutions so that the system can function well even in oxygen-lean environments under the realistic working conditions of PEMFCs. Taking this into account, we introduce Pt/SiO2@CeO2-30%, an engineered electrocatalyst with potentially generated oxygen vacancies (Ov), which can immensely contribute toward the enhancement in the O2 availability in oxygen-lean conditions like the air feed conditions, allowing an effective control of the overpotential related to the oxygen reduction reactions (ORRs) at the electrode level. The meticulously crafted Pt-CeO2 interface serves as one of the appreciable structural attributes of the present catalyst, facilitating oxygen spillover toward the Pt environment, aided by the creation of the immense Ov along the nano CeO2 phase of the catalyst. In addition to the benefit of addressing the oxygen-lean conditions and overcoming the limitations of the state-of-the-art catalysts, usage of a noncarbonaceous support like SiO2 to house the Pt and CeO2 nanoparticles has been anticipated to lessen the corrosion problems, a major drawback associated with the carbon-based ORR catalysts. Apart from this, a significant contribution of SiO2 to the self-humidification of the ionomer interface plays a crucial role in enabling the MEA to work under low relative humidity conditions, which can be attributed to an additional benefit of the current composition of the catalyst. The catalyst demonstrated a promising ORR performance with a substantial improvement in H2-air feed circumstances and better corrosion resistance when tested with a membrane electrode assembly (MEA) in a single-cell configuration, illustrating the practical feasibility in a realistic system-level validation.
Keywords: carbon corrosion; carbon-free electrocatalyst; oxygen buffering; oxygen reductionreaction; oxygen spill over; protonexchange membrane fuel cell